Hematuria and a complex congenital heart defect in a newborn foal - Spiro, Illana (2002)
A 16-hour-old foal was referred for evaluation of hematuria. A pansystolic heart murmur and left thoracic thrill were detected; laboratory diagnostics and ultrasonography identified a complex congenital heart defect. The diagnosis was confirmed at postmortem.